Microbiological conditions for culturing Helicobacter Pylori (2013)
Early diagnosis and culturing of Helicobacter pylori are of great importance for the study of the growth characteristics of these bacteria which can contribute to knowledge of classical and molecular epidemiology, genetic diversity and susceptibility to antibiotics. The ubiquity and importance of this pathogen throughout the world has forced us to consider and propose effective routine alternatives for isolating and identifying these bacteria in microbiology laboratories. This review was conducted to describe the literature concerning the conditions for cultivation of this organism in the laboratory.